Asset Recovery of Detrimental to The Finances of The State From Proceeds of Corruption in The Development of National Criminal Law System - Eri Satriana; Dewi Kania Sugiharti; Muhammad Ilham Satriana (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Asset Recovery resulting from corruption in Law 31/1999 in conjunction with Law 20/2001 is difficult, besides that Indonesia, which has ratified UNCAC 2003, is still experiencing difficulties resulting in a low amount of repayment of state financial losses compared to its own financial losses. Problems in asset recovery originate from Article 18 of Law 31/1999 in conjunction with Law 20/2001, which can only be done after a court decision has permanent legal force. UNCAC 2003 has the concept of non conviction base forfeiture (in brake system) to overcome these weaknesses. The formulation of optimizing punishment is generated by asset recovery with an economic analysis of law approach using the time value of money as a determinant of calculationKeywords: asset recovery; detrimental to the finances of the state; corruption; national criminal law system.